If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 32 = 0.22x Reorder the terms: 32 + 2x = 0.22x Solving 32 + 2x = 0.22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.22x' to each side of the equation. 32 + 2x + -0.22x = 0.22x + -0.22x Combine like terms: 2x + -0.22x = 1.78x 32 + 1.78x = 0.22x + -0.22x Combine like terms: 0.22x + -0.22x = 0.00 32 + 1.78x = 0.00 Add '-32' to each side of the equation. 32 + -32 + 1.78x = 0.00 + -32 Combine like terms: 32 + -32 = 0 0 + 1.78x = 0.00 + -32 1.78x = 0.00 + -32 Combine like terms: 0.00 + -32 = -32 1.78x = -32 Divide each side by '1.78'. x = -17.97752809 Simplifying x = -17.97752809
| 3(x-1)=-2/3(x-3) | | -3v+v=8(9-v)-3(6-4v) | | -14=18(-z-2)-4(3z-9) | | 4(5n-8n)=-40-2n | | 3x/4=-36 | | 7x+5-2x+8(x-3)=4x-[5x-(2+3x)] | | (2b^3/a)^2= | | 3a+3a+3a+3a+6*2a= | | 2x+y=15-5x | | S=6(15)+110 | | 6t-1=6t-5 | | 2x+3=48-6 | | 23+4h+7h-h+2y-10=10h+2y+13 | | x(3x-7)=(3x+5)(x-3) | | x^4-14x^2+44=0 | | 10/11x-5=6 | | 6n+6=6-6(-7n-6) | | [10/11x-5]=6 | | 1=.3x-.5x-7 | | 7+4x=6x+7 | | x^2-14x+34=10 | | .6n+.4(n-.3)=-2.67 | | (6x-17)-(-6x+9)= | | 4(p-7)+6(p-23)=14 | | b-3b+2*2b-4b= | | 27=x/2+15 | | -x+40=28 | | (2w+6)w=216 | | 6(4s+12)=(3s-14) | | 1/3y-6x=4 | | 5+2x+8=x+7 | | 8+(3a-24)=(4a+20) |